Associations of SF-36 mental health functioning and work and family related factors with intentions to retire early among employees. Issue 8 (6th April 2006) - Harkonmäki, K; Rahkonen, O; Martikainen, P; Silventoinen, K; Lahelma, E
Abstract : Objective: To examine the associations of mental health functioning (SF-36) and work and family related psychosocial factors with intentions to retire early. Methods: Cross sectional survey data (n = 5037) from the Helsinki Health Study occupational cohort in 2001 and 2002 were used. Intentions to retire early were inquired with a question: "Have you considered retiring before normal retirement age?" Mental health functioning was measured by the Short Form 36 (SF-36) mental component summary (MCS). Work and family related psychosocial factors included job demands and job control, procedural and relational justice, conflicts between work and family, and social network size. Multinomial regression models were used to analyse the data. Results: Poor mental health functioning, unfavourable psychosocial working conditions, and conflicts between work and family were individually related to intentions to retire early. After adjustments for all work and family related factors the odds ratio for low mental health functioning was halved (from OR = 6.05 to 3.67), but nevertheless the association between poor mental health functioning and strong intentions to retire early remained strong. Conclusions: These findings highlight not only the importance of low mental health and unfavourable working conditions but also the simultaneous impact of conflicts between work and family to employees' intentions to retire early.